2017
DOI: 10.17750/kmj2017-27
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic features of the macrotypes of chronic endometritis

Abstract: Aim. To expand the understanding of the pathogenesis of chronic endometritis based on the study of reception and markers of cell proliferation/apoptosis in its various macrotypes depending on the nature of microbial colonization.Methods. We prospectively examined a group of 345 women with early reproductive losses (history of missed miscarriage, spontaneous abortion, artificial abortion, in vitro fertilisation failures during up to 6 months after intrauterine intervention), who had histologically verified chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Endometrial hyperplastic processes are registered in almost every third patient in groups with uterine fibroids (38.1%), adenomyosis (39.2%), in every second patient with a combination of three nosologies (43.5%). Endometrial polyps were found more often: practically in two-thirds (61.3%) with certain nosology and in every second woman (56.4%) with their combination [ 4 , 5 , 7 , 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endometrial hyperplastic processes are registered in almost every third patient in groups with uterine fibroids (38.1%), adenomyosis (39.2%), in every second patient with a combination of three nosologies (43.5%). Endometrial polyps were found more often: practically in two-thirds (61.3%) with certain nosology and in every second woman (56.4%) with their combination [ 4 , 5 , 7 , 12 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the leading factors, the following disorders should be noted: extragenital diseases (thyroid dysfunction, overweight, pathology of the gastrointestinal tract, cardiovascular disease) and comorbidity of gynecological pathology (leiomyoma, adenomyosis, polycystic ovary syndrome, benign ovarian tumors [ 9 , 11 14 ]. It is necessary to emphasize recent data on the growth of chronic endometritis (CE) as one of the factors in the development of HPE [ 11 , 12 , 15 , 16 ]. Against the background of pelvic inflammatory disease and hormonal imbalance, there is a probability of developing pathological processes in the ovaries [ 1 – 3 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of bacterium-virus colonization in endometrium, as a rule, results from inability of the immune system and nonspecific body defenses (complement system, phagocytosis) to eliminate an infectious agent entirely, which leads to microorganisms persistence characterized by the appearance of mononuclear phagocytes, natural killer cells, synthesizing proinflammatory cytokines in the area of inflammation [10,17].…”
Section: Discussionmentioning
confidence: 99%
“…By consensus of obstetricians and gynaecologists in 2006 each case of nondeveloping pregnancy is regarded as being associated with chronic endometritis, both at the cause and the effect levels [7] Latest research has shown that chronic pelvic inflammatory diseases are not accompanied by disruption of parameters of cellular and humoral immunity detected in peripheral blood. Thus, in order to determine functional status of endometrium, we need to assess the local immunity [8][9][10]. Bacterium-virus colonization of endometrium is the result of failure of the immune system to eliminate infectious agent; but at the same time its spread is limited due to effector properties of Tlymphocytes, NK-cells and macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent innovations in stimulation protocol schemes, reproductive immunology, culture medium, technical equipment, and application of preimplantation genetic testing, implantation and genetic health of embryos remain the leading cause behind the effective implementation of IVF programs [15,23,24].…”
mentioning
confidence: 99%